FACTORS CAUSING THE ACCURACY OF THE WITHDRAWAL PLAN - Susilo, Budi; Trisulo, Trisulo (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
The purpose of the study is to determine the quality of budget planning through the analysis of the suitability of the realization of absorption or withdrawal of funds to the Fund Withdrawal Plan (RPD). This study uses a qualitative descriptive method, primary data is obtained from interviews and secondary data comes from documents at the Solok State Treasury Service Office (KPPN). The results of the study show that the accuracy of cash planning and the quality of budget absorption in work units are still relatively low. Lack of budget planning is caused by weak coordination between planning and implementing activities in work units, human resource behavior lacks a sense of responsibility for financial managers, and the absence/weakness of the reward and punishment system is also a factor in the low quality of budget planning.